Heterogeneous mechanomyographic absolute activation of paraspinal muscles assessed by a two-dimensional array during short and sustained contractions - Madeleine, Pascal; Tuker, Kylie; Arendt-Nielsen, Lars; Farina, Dario (Journal of biomechanics, 2007)
Spatial dependency of paraspinal muscle activity was assessed using a new two-dimensional MMG recording system. MMG signals were detected over the left and right paraspinal muscles of 10 volunteers using a grid of 12 accelerometers. During two separate trials subjects maintained a 20° flexed position and held loads that ranged from 0 to 15 kg (in 2.5 kg increments) for 20 s; and 7.5 kg for 6 min. Maps of absolute and normalised (with respect to initial values) average rectified value, mean power frequency, variance and skewness of the power spectral density were obtained from the two-dimensional MMG recordings. For both the short duration and sustained contractions, the MMG absolute average rectified value, mean power frequency, variance and skewness depended on accelerometer location ( P<0.05), while, with the exception of the skewness ( P<0.05), normalised values did not. These results demonstrate both inhomogeneous MMG absolute activity and homogeneous MMG normalised activity in paraspinal muscles for short duration and sustained contractions. Moreover, the effect of accelerometer location on spectral variables confirmed the limited validity of general relationships between MMG spectral changes and motor unit recruitment strategies. This study underlines the importance of using multiple recording sites when assessing back muscle activity.